THE IMPACT OF BRAND AWARENESS AND PERCEIVED QUALITY ON GREEN COSMETICS PURCHASE INTENTION IN MANADO - Lala, Ryanna Jasmine; Tulung, Joy E.; Wangke, Shinta J. C. (Universitas Sam Ratulangi, 2024)
This study examines the relationship between brand awareness and perceived quality on purchase intention among users of green cosmetics. Using a quantitative approach, data was collected through questionnaires and observations. The research instruments were tested for validity and reliability. Multiple linear regression, hypothesis testing, and classical assumptions were applied to analyze the data. The results show that brand awareness has a positive and significant effect on purchase intention. Additionally, perceived quality also has a positive and significant effect on purchase intention. Furthermore, the simultaneous effect of brand awareness and perceived quality on purchase intention is also significant. The study concludes that brand awareness and perceived quality simultaneously influence purchase intention among users of green cosmetics. It is recommended that green cosmetics companies focus on increasing brand awareness and perceived quality to increase purchase intention among their target audience. Keyword: Green Cosmetics, Brand Awareness, Perceived Quality, Purchase Intention